Applying Remote Sensing Technology and Geographic Information System in Batu, East Java - Rudi Hartono; Nasikh Nasikh (Faculty of Geography, Universitas Gadjah Mada, 2017)
This research is aimed to map potential landslide areas, identify types of the landslide, and draw a map of potential landslide level. This research was carried out in Batu, East Java. The research design that was used in the study was image interpretation of Landsat 7 Band 432 Satellite and primary data of the landslide causes (the data of soil and rocks, map interpretation, and variable scoring of the landslide. ArcGIS 9.3 and ArcView 3.2 software was used for map analysis. The researcher also analyzed the soil texture, permeability and land plasticity index, bedding, weathering level, the density of joints, the depth of weathering, the existence of springs, slopes, and slope cutting. The research findings showed that the image of Landsat 7 Bands 432 in 1:11.000 – 1:15.000 scale could be used to interpret land use and land cover. Interpreted land use included housing, bare soil, irrigated rice field, rain-fed rice field, moor, nursery area, garden, slope failure, natural forest, sengon forest, pine forest, and agroforestry.